Shaping the normative landscape - Owens, David (Oxford : Oxford University Press, 2012)
'Shaping the Normative Landscape' is an investigation of the value of obligations and of rights, of forgiveness, of consent and refusal, of promise and request. David Owens shows that these are all instruments by which we exercise control over our normative environment.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social sciences -- Philosophy; Social norms